Forged in the shadow of Mars: chivalry and violence in late medieval Florence - Sposato, Peter (Cornell University Press, 2022)
"Challenges the current understanding of elite culture in late medieval Florence by arguing that chivalric ideology, traditionally considered by scholars to be foreign to the social and cultural landscape of late medieval Italian cities, played a major role in shaping the mentality and behavior of many Florentine elites, especially members of ancient lineages. This book offers the first examination of chivalric culture and its practitioners, who played an important but understudied role in the transformation of Florence into the dominant territorial state in north-central Italy"--